SCREEN TIME AND PHYSICAL ACTIVITY ASSOCIATED WITH QUALITY OF LIFE AND MENTAL HEALTH OF FEDERAL NETWORK EMPLOYEES: A CROSS-SECTIONAL STUDY (CIPEEX, 2025)
Ensuring quality of life (QoL) and mental health for employees is crucial for promoting a healthy and productive work environment, especially within the educational sector. However, physical inactivity and screen time are prevalent among this population. To assess the association between screen time and physical activity (PA) with QoL and mental health among employees of Brazil’s Federal Network of Education. This is an epidemiological cross-sectional study conducted from June to November 2022. The sample included 1,563 employees from the Brazilian Federal Network. The WHOQOL-bref and DASS-21 questionnaires were used to assess the dependent variables. The study was approved by the Research Ethics Committee of the Federal Institute of Goiano – Ceres Campus (Approval No. 5.270.596). Statistical analyses were performed using SigmaPlot software (version 14.0). The results showed that 57.5% of the sample were female, and 55.6% engaged in regular PA, presenting fewer symptoms of depression, anxiety, and stress (p < 0.001). Additionally, 76.9% reported spending five or more hours per day on a computer, and these participants had higher levels of depression (p = 0.002) and anxiety (p = 0.016). Those who engaged in regular PA showed better QoL across all WHOQOL-bref domains (p < 0.001). Conversely, those who watched TV or used a computer for five or more hours per day reported worse QoL in the physical, psychological (p < 0.05), and environmental (p < 0.002) domains. The current findings highlight the need for targeted intervention strategies for employees in Brazilian education to promote increased physical activity and reduced screen time, aiming to enhance QoL and mental health in this population.
Keywords: Quality of life; Mental health; Sedentary behavior; Educational workers